(untitled) (Forum Penelitian Agro Ekonomi, 2024)
From the viewpoint of historical perspective Indonesia has experienced three generations of water law namely Algemeen Water Reglement (general water law), year 1936, Law No 11 of 1974 and Law No 7 Year 2004 on water resources. The purpose of this paper is to study factors considered as the drivers of the emergence of each generation of law. The analysis of historical context identified the dominant factors. The three generations of law are driven by various factors in response to the emerging political interests. In the first, ethical politics, development of hydraulic technology, and the interest to support agricultural export commodity are important driving factors. In the second, green revolution technologies, and the political interest to achieve rice self- sufficiency are dominant factors while that of the third is influenced by politics of bureaucracy in the aftermath of economic crisis of 1998, economic liberalization as condition for the World Bank loan, and global political pressure to implement integrated water resources management. By the cancelation of the third generation of law Indonesia is stepping toward the fourth generation of law which has to be prepared in accountable manner based on the principles of good water governance.